A produção técnica na Universidade Federal de São Carlos : identificação para comunicação no repositório institucional - Corrêa, Tiago Silva (Universidade Federal de São Carlos, 2017)
The enormous amount of intellectual production inside universities makes important to spread and preserve it. Therefore we have the concept of institutional repositories. The repositories developed by higher education institutions display works of academic character and doctoral thesis, master's dissertations and scientific articles. However, other types of production, as the technical one, can also be added to a repository. This study aimed to identify the types of technical productions existing in the Federal University of São Carlos, in which the technical productions elaborated by university professors and the technical administrative production was highlighted. To identify these technical productions, the Lattes Platform was used, which developed by CNPq and provides access and standardization of academic and professional records of the researches who work in the Brazilian territory. The scriptLattes tool was used to extract and visualize the data obtained from the curriculums. The period analyzed was from 1968 to September 2016. From the 1.296 professors at the Federal University of São Carlos, 1.291 have Lattes curriculum. The extraction of the professors' data resulted in 24.832 productions. From the 1.014 administrative technicians of the Federal University of São Carlos, 510 have curriculum on the Lattes Platform, the extraction of the technicians' data resulted in 866 productions. A hundred different types of technical production were identified from the extracted data from the professors and technicians. The technical and administrative production was also verified in the proceeding of the various internal administrative documents, by using the Sistema Tramite (Proceeding System), which provides the document types proceeded inside the University. To identify the documents with intellectual or historical value, the temporality tables of the Archive National Council were applied. Therefore, we found 165 types of documents with temporality indication of 47 years or permanent guard.
Keywords: Produção intelectual; Produção técnica; Repositório institucional; ScriptLattes; Intellectual production; Technical production; Institutional repository; OUTROS